Structural synaptic elements are differentially regulated in superior temporal cortex of schizophrenia patients - Schmitt, Andrea; Spanagel, Rainer; Zink, Mathias; Gebicke-Härter, Peter J. (European archives of psychiatry and clinical neuroscience, 2012)
Inaccurate wiring and synaptic pathology appear to be major hallmarks of schizophrenia. A variety of gene products involved in synaptic neurotransmission and receptor signaling are differentially expressed in brains of schizophrenia patients. However, synaptic pathology may also develop by improper expression of intra- and extra-cellular structural elements weakening synaptic stability. Therefore, we have investigated transcription of these elements in the left superior temporal gyrus of 10 schizophrenia patients and 10 healthy controls by genome-wide microarrays (Illumina). Fourteen up-regulated and 22 downregulated genes encoding structural elements were chosen from the lists of differentially regulated genes for further qRT-PCR analysis. Almost all genes confirmed by this method were downregulated. Their gene products belonged to vesicle-associated proteins, that is, synaptotagmin 6 and syntaxin 12, to cytoskeletal proteins, like myosin 6, pleckstrin, or to proteins of the extracellular matrix, such as collagens, or laminin C3. Our results underline the pivotal roles of structural genes that control formation and stabilization of pre- and post-synaptic elements or influence axon guidance in schizophrenia. The glial origin of collagen or laminin highlights the close interrelationship between neurons and glial cells in establishment and maintenance of synaptic strength and plasticity. It is hypothesized that abnormal expression of these and related genes has a major impact on the pathophysiology of schizophrenia.